PENGARUH PERCEIVED USEFULNESS, EASE OF USE, DAN TRUSTWORTHINESS TERHADAP INTENTION TO USE DIGITAL PAYMENT OVO PADA MAHASISWA S1 DAN D4 FEB UNIVERSITAS NEGERI JAKARTA PERIODE 2024 - Farhan Fadilah Siregar; Hakim Nur Rahman, Kautsar Naufa Haykal, Krishna Widwi Aiyub Ilyasa, Muhamad Bayuaji Satria Prabowo (Jurnal Ekonomi dan Bisnis, 2025)
In this digital era, e-wallets are no longer viewed as an alternative, rather an essential solution to daily transaction needs. OVO which stood as the second-most downloaded e-money application in 2024, raises questions as to which factors that drive the popularity of this application. Therefore, this study aims to explain the intention to use of OVO through a number of independent variables such as Perceived Usefulness, Ease of Use, and Trustworthiness as proxy. This study was conducted on students of S1 and D4 FEB of UNJ that are still active during the year 2024. This study uses quantitative approach in a form of an online questionnaire distributed via whatsapp, and through purposive sampling obtained 76 samples which consists of 41 men and 35 women. Questionnaire consisted of 25 questions spread in value using Likert scale model, which gives a range of 1 (Strongly Disagree) to 6 (Strongly Agree). Model used is multiple linear regression utilizing SPSS Version 27. The model results in a regression value of R Square 0.548, alongside partial test (t test) of each independent variable which indicated a positive and significant relation (t Value > t Table, Sig. < 0.05), and a simultaneous test (f test) which indicated all independent variables simultaneously has a positive and significant relation (f Value > f Table, Sig. < 0.05) to intention of use.